The Use of Medium-Chain Triglyceride in Children with Intestinal Malabsorption - Michael Gracey (Paediatrica Indonesiana, 1974)
The comments which followare a brief summary of the thera-peutic place of MCT in children withmalabsorption. This will be followedby some remarks about the potentialvalue of MCT in countries like Indo-nesia where the commonest cause ofchronic diarrhoea and malabsorptionin children is malnutrition and chro-nic and repeated gastrointestinal in-fections and infestations and whereMCT has not been used widely.